Pharmacoeconomic Aspects of Diabetes Mellitus: Outcomes and Analysis of Health Benefits Approach - Baishnab, Suman; Jaura, Ravinder S.; Sharma, Saksham; Garg, Honey; Singh, Thakur Gurjeet (Current Diabetes Reviews, 2024)
Pharmacoeconomics is an important tool for investigating and restructuring healthcare policies. In India, recent statistical studies have shown that the number of diabetic patients is rapidly increasing in the rural, middle and upper-class settings. The aim of this review is to call attention towards the need to carry out pharmacoeconomic studies for diabetes mellitus and highlight the outcome of these studies on healthcare. A well-structured literature search from PubMed, Embase, Springer, ScienceDirect, and Cochrane was done. Studies that evaluated the cost-effectiveness of various anti-diabetic agents for type 2 diabetes were eligible for inclusion in the analysis and review. Two independent reviewers sequentially assessed the titles, abstracts, and full articles to select studies that met the predetermined inclusion and exclusion criteria for data abstraction. Any discrepancies between the reviewers were resolved through consensus. By employing search terms such as pharmacoeconomics, diabetes mellitus, cost-effective analysis, cost minimization analysis, cost-utility analysis, and cost-benefit analysis, a total of 194 papers were gathered. Out of these, 110 papers were selected as they aligned with the defined search criteria and underwent the removal of duplicate entries. This review outlined four basic pharmacoeconomic studies carried out on diabetes mellitus. It gave a direction that early detection, patient counseling, personalized medication, appropriate screening intervals, and early start of pharmacotherapy proved to be a cost-effective as well as health benefits approach.
Keywords: cost analysis